The importance of imagery in acquiring and improving motor skills and sports technique - Petrica, J.; Duarte-Mendes, P.; Marinho, D. (Journal of Human Sport & Exercise, 2019)
Imagery, in a simplistic way, is the mental image we have of movement. In order to understand whether there is an association between the imagery capability, as the ability we have to see and mentally feel the movement, and motor activity, we have been developing some complementary works seeking to better understand its relation with dribbling, passing, ball handling and shooting in football, with the technical skills of Basketball, with different levels of sports performance in swimming, and even with global and fine praxis or balance in individuals with disabilities and also to see if the gender has any relation to it. Using MIQ-3 as the main working instrument and specific motor tests for the skills to study, some works with different samples were carried out in a complementary logic that would allow us to better understand the extent of the importance of the study relationship and for which several statistical techniques were used, such as the Kaiser-Meyer-Olkino sampling adequacy measure, the Bartlett sphericity test, the exploratory factorial analysis, the Kolmogorov-Smirnov test, the Shapiro-Wilk test, the T-Student, the T-Test and the Mann-Whitney and Wilcoxon tests, as appropriate. We conclude that in most studies there is a clear association between imagery capacity and performance, achievement, or motor improvement.